A Rare Case of Idiopathic Atrophoderma of Pasini and Pierini - Hui Xiao; Sushmita Pradhan; Xingchun Yang; Jiaxiu Liu; Tangyou Zhu (Nepal Journal of Dermatology, Venereology & Leprology)
Idiopathic atrophoderma of Pasini and Pierini (IAPP) is a rare pigmented atrophic cutaneous disease. Here, we report a case of a 27-year-old woman who presented with asymptomatic brown patches on her upper back for one year. There was no prior history of swelling or induration of the lesions. Physical examination showed atrophic patches with clear boundaries, consistent with snow footprints or cliff-drop-like changes on edge. Dermoscopy revealed numerous bare linear, branched blood vessels and perifollicular brownish areas, which differs from only one previously reported IAPP. Biopsy showed perivascular mononuclear cells infiltrating the dermis and reduced elastic fibers in the upper and middle dermis. Typical clinical findings of “footprints in the snow” appearance and dermoscopy could combine for a definite diagnosis aiding in differentiating from morphea presenting with whitish structureless and hairless areas. This case report might stimulate clinicians to diagnose such a rare disease in patients with similar lesions to avoid unnecessary treatment.